Keeping track of who said what: Performance on a modified auditory n-back task with young and older adults - Kidd, Gary R.; Humes, Larry E. (Frontiers in Psychology, 2015)
A modified auditory n-back task was used to examine the ability of young and older listeners to remember the content of spoken messages presented from different locations. The messages were sentences from the Coordinative Response Measure (CRM) corpus and the task was to judge whether a target word on the current trial was the same as in the most recent presentation from the same location (left, center, or right). The number of trials between comparison items (the number back) was varied while keeping the number of items to be held in memory (the number of locations) constant. Three levels of stimulus uncertainty were evaluated. Low- and high-uncertainty conditions were created by holding the talker (voice) and non-target words constant, or varying them unpredictably across trials. In a medium-uncertainty condition, each location was associated with a specific talker, thus increasing predictability and ecological validity. Older listeners performed slightly worse than younger listeners, but there was no significant difference in response times (RT) for the two groups. An effect of the number back (n) was seen for both PC and RT; PC decreased steadily with n, while RT was fairly constant after a significant increase from n = 1 to n = 2. Apart from the lower PC for the older group, there was no other effect involving age for either PC or RT. There was an effect of target word location (faster RTs with a late-occurring target) and an effect of uncertainty (faster RTs with a constant talker-location mapping, relative to the high-uncertainty condition). A similar pattern of performance was observed with a group of elderly hearing-impaired listeners (with and without shaping to ensure audibility), but RTs were substantially slower and the effect of uncertainty was absent. Apart from the observed overall slowing of RTs, these results provide little evidence for an effect of age-related changes in cognitive abilities on this task.